2011
DOI: 10.4149/km_2011_6_417
|View full text |Cite
|
Sign up to set email alerts
|

The influence of PWHT regime on microstructure and creep rupture behaviour of dissimilar T92/TP316H ferritic/austenitic welded joints with Ni-based filler metal

Abstract: In this paper the dissimilar welded joints between the ferritic (tempered martensitic) steel T92 and the non-stabilised austenitic steel TP316H were investigated in terms of microstructure and creep rupture behaviour characterisation. The welded joints were prepared by the TIG method using the Ni-based filler metal Nirod 600 (Inconel-type). After the welding, the individual weldments were subjected to the two different regimes of post-weld heat treatment (PWHT), either the "classical" PWHT (i.e. subcritical te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
(39 reference statements)
2
19
0
Order By: Relevance
“…2b and 4). Detailed microstructural analysis of Nirod 600 weld metal was performed in our previous studies on T92/TP316H weldments [39,40].…”
Section: Microstructure In Pwht Statementioning
confidence: 99%
“…2b and 4). Detailed microstructural analysis of Nirod 600 weld metal was performed in our previous studies on T92/TP316H weldments [39,40].…”
Section: Microstructure In Pwht Statementioning
confidence: 99%
“…In general, the HAZ region with its strongly heterogeneous microstructure, so-called "HAZ microstructural gradient", is considered to be the critical region of welded joints because of its high propensity for several types of cracking and final failure occurrence [9,10]. The findings of our several former studies about dissimilar T92/TP316H weldments [11][12][13][14] have clearly indicated that the HAZ microstructural heterogeneity can be efficiently suppressed by the application of unconventional "quenching-and-tempering" post-welding heat treatment (QT PWHT). In contrast to microstructural characteristics obtained after conventional "tempering" PWHT (T PWHT), the microstructures of welded base materials after performing QT PWHT became coarser and homogenized with respect to the grain size and state of secondary phase precipitation.…”
Section: Introductionmentioning
confidence: 83%
“…The same precipitates were indicated in Thermanit Nicro 82 weld metal. Moreover, these precipitates were extracted in carbon replicas and analysed in TEM by SAED technique [15]. It has been confirmed that these precipitates exhibit face-centered cubic crystal structure.…”
Section: Methodsmentioning
confidence: 98%